Avaliação espaço-temporal da atividade antrópica no estuário do rio Sergipe - Santos, Danielle Gois Moreira (2012)
In this study we investigated the composition of the sediment from Sergipe River Estuary, located in the metropolitan area of Aracaju, in two periods: the winter of 2010 and the summer of 2011. In the recent years, this river has been undergoing a process of degradation due to release of sewage, without proper treatment, and the process of industrialization in its basin. We performed the sediments characterization from the analysis of total organic carbon (TOC), total organic matter (TOM), total nitrogen (TN) and the amount of silt, clay and sand. The lipid compounds, such as sterols and linear alcohols, were identified and quantified in extracts of surface sediments in the Sergipe River Estuary by gas chromatography coupled to mass spectrometry (GC-MS). The autochthonous and allochthonous contributions were characterized in the study area through the determination of sterols and alcohols in sediments. The autochthonous contribution was determined using the amount and distribution of the linear alcohols of short chain (<C20), which characterize the presence of aquatic organisms such as algae and bacteria. The allochthonous contribution was evidenced by the presence of linear long chain alcohols (> C20) and the identification of sterols of 29 carbon atoms. The C30 alcohol was the compound which presented the higher concentration within all samples, with values ranging from 0.62 to 2.46 μg.g-1 in the winter and 0.37 to 21.41 μg.g-1 in the summer. The most prominent sterol concentration was observed for β-sitosterol (C29), in concentrations ranging from 1.15 to 15.69 μg.g-1 in the winter and from 1.23 to 8.09 μg.g-1 in the summer. These compounds are frequently found in large quantities in vascular plants. Therefore, suggesting a strong contribution of terrigenous materials to the estuary. Contamination by sewage in the Sergipe River estuarine system was assessed by the presence of coprostanol (fecal biomarker) in the sediments and the different sterols ratios and indexes. This contamination was attributed to the possible discharge of untreated sewage into the Sergipe river basin.